Laser safety : practical knowledge and solutions - Barat, Ken (IOP (Series). Release 6., 2019)
Laser Safety: Practical Knowledge and Solutions / provides an in-depth guide to laser safety for a wide variety of people who work regularly with lasers and similar products. Laser safety basics will be discussed within the book with an explanation of laser safety devices and useful techniques to obtain workable laser safety culture. An expansion of topics not found in the typical laser safety text includes ergonomics, mentoring, performance-based learning, on the job training, laser safety tools and solutions as well as laser disposal guidance. Considering risk analysis approaches and functional methods for laser application, and a look at making presentations more universally readable, this book will be relevant to students, researchers and laser physicists. Part of / IOP Series in Coherent Sources and Applications.